2016
DOI: 10.18203/issn.2455-4510.intjresorthop20164411
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment in children missed Monteggia lesions at Bhuj, Kutch, Gujarat: a retrospective study

Abstract: <p class="abstract"><strong>Background:</strong> The treatment of an unrecognized Monteggia lesion continues to pose a therapeutic challenge, as evidenced by the variety of surgical techniques described. Moreover, there are high complication and redislocation rates following surgery. This report concerns a surgical technique to reduce a chronic dislocation of the radial head utilizing an ulnar osteotomy and internal fixation<span lang="EN-IN">.</span></p><p class="abstrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…13,14 Also, distraction and angulation at the osteotomy site pushes the radial head down through the interosseous membrane, eliminating for any ligament reconstruction requirement. 15,16 There are two studies in which only ulnar osteotomy is done 17,18 In study of Parkash, angulation and elongation of the ulna by ulnar osteotomy are required for reduction of the radial head and this is same in our study. In study of Park et al, ulnar osteotomy and correction of the ulnar deformity are the key components to achieve reduction and this is also true in our study Another study showed both ulnar ostetomy and annular ligament reconstruction are required.…”
Section: Discussionsupporting
confidence: 51%
“…13,14 Also, distraction and angulation at the osteotomy site pushes the radial head down through the interosseous membrane, eliminating for any ligament reconstruction requirement. 15,16 There are two studies in which only ulnar osteotomy is done 17,18 In study of Parkash, angulation and elongation of the ulna by ulnar osteotomy are required for reduction of the radial head and this is same in our study. In study of Park et al, ulnar osteotomy and correction of the ulnar deformity are the key components to achieve reduction and this is also true in our study Another study showed both ulnar ostetomy and annular ligament reconstruction are required.…”
Section: Discussionsupporting
confidence: 51%
“…Synostosis was observed in one patient in the series by Oner and Diepstraten [46] , although no ulnar osteotomy was carried out. Dissection during open reduction of the radial head appears to be a greater risk factor for proximal synostosis.…”
Section: Complicationsmentioning
confidence: 93%
“…3,6,12,22 On the contrary, successful closed radial head repositioning has been documented by some authors. [17][18][19][20]…”
Section: Open Versus Closed Reductionmentioning
confidence: 99%
“…Reduction of the radial head can be achieved by an open approach or without opening the joint. [17][18][19][20] No consensus has yet been reached regarding the necessity for the several steps in this surgical procedure. Therefore, work-up to surgery is also still unclear; it is unknown whether dysmorphic features of the radial head are a contraindication for surgery or whether time between trauma and surgery is of influence on surgical outcome.…”
Section: Introductionmentioning
confidence: 99%